The Prognostic and Clinical Value of CD44 in Colorectal Cancer: A Meta-Analysis - Wang, Zhenpeng; Tang, Yufei; Xie, Lei; Huang, Aiping; Xue, Chunchun; Gu, Zhen; Wang, Kaiqiang; Zong, Shaoqi (Frontiers in Oncology, 2019)
Background: CD44 is widely used as a putative cancer stem cells (CSCs) marker for colorectal cancer (CRC). However, the prognostic role of CD44 in CRC remains controversial. Methods: We performed a systematic review and meta-analysis to evaluate the association of various CD44 isoforms and overall survival (OS) and clinicopathological features of CRC patients. Results: A total of 48 studies were included in the meta-analysis. Total CD44 isoforms overexpression was significantly correlated with worse OS of patients with CRC (HR=1.32,95%CI=1.08-1.61). In stratified analysis, a higher level of either CD44v6 or CD44v2 had an unfavorable impact on OS (HRCD44v6=1.50,95%CI=1.10-2.14; HRCD44v2=2.93,95%CI=1.49-5.77). Additionally, CD44 was shown to be associated with some clinicopathological features, such as poor differentiation (ORTotal CD44 isoforms=1.44,95%CI=1.00-2.08), lymph node metastasis (ORCD44=1.56,95%CI=1.01-2.41; ORCD44v6=1.97,95%CI=1.19-3.26; ORTotal CD44 isoforms=1.57,95%CI=1.15-2.14), distant metastasis (ORCD44=2.90,95%CI=1.08-7.83; ORTotal CD44 isoforms=1.89,95%CI=1.02-3.53). Moreover, elevated level of CD44v6 tend to be correlated with tumor size (OR=1.71,95%CI=0.99-2.96). Conclusions: This meta-analysis demonstrated that CD44 overexpression might be an unfavorable prognostic factor for CRC patients and could be used to predict poor differentiation, lymph node metastasis and distant metastasis.